Drought or/and Heat-Stress Effects on Seed Filling in Food Crops: Impacts on Functional Biochemistry, Seed Yields, and Nutritional Quality - Sehgal, Akanksha; Sita, Kumari; Siddique, Kadambot H. M.; Kumar, Rakesh; Bhogireddy, Sailaja; Varshney, Rajeev K.; HanumanthaRao, Bindumadhava; Nair, Ramakrishnan M.; Prasad, P. V. Vara; Nayyar, Harsh (Frontiers in Plant Science, 2018)
Drought and heat (high temperatures) stress are the prime abiotic stresses, under the current and future climate change scenarios. Any further increase in the occurrence, and extremity of these stresses either individually or in combination,would severly reduce the crop productivity and global food security. Although, these stresses obstruct productivity at all growth stages, however, the extent of damage at reproductive phase of crop growth, especially the seed filling phase, is critical and causes considerable yield losses. Heat and drought stress substantially affect the seed yields by reducing seed size and number, eventually affecting the commercial trait ‘100 seed weight’ and seed quality. Seed fiiling is influenced by various processes occurring in the leaves, especially production and export of photoassimilates, importing precursors for biosynthesis of seed reserves, minerals and other constituents. These processes are highly sensitive to various environmental stresses, including heat and drought, due to involvement of several diverse enzymes and trasnporters, located in the leaves and seeds. We present here the findings in various food crops showing how their seed composition is drastically impacted at various cellular levels due to drought and heat stress, applied individually, or in combination. The combined drought and heat stress are found to be extremely detrimental for seed yield and its quality, and thus need more attention in food crops. Understanding the prescise target sites regulating the seed filling events in leaves and seeds, and how they are affected by abiotic stresses is imperative to improve seed quality. It is vital to understand the physiological, biochemical and genetic mechanisms, which govern the various events influencing seed filling under stress enveironments to devise strategies to improve stress tolerance. Converging modern advances in physiology, biochemistry and biotechnology, especially the “omics” technologies might improve our understanding about these apects. Application of knowledge from these technological developments along with effective agronomic management would provide impetus in developing crop varieties with improved productivity under drought and heat stresses.